2016
DOI: 10.1177/1535370216681549
|View full text |Cite
|
Sign up to set email alerts
|

Major involvement of bacterial components in rheumatoid arthritis and its accompanying oxidative stress, systemic inflammation and hypercoagulability

Abstract: We review the evidence that infectious agents, including those that become dormant within the host, have a major role to play in much of the etiology of rheumatoid arthritis and the inflammation that is its hallmark. This occurs in particular because they can produce cross-reactive (auto-)antigens, as well as potent inflammagens such as lipopolysaccharide that can themselves catalyze further inflammagenesis, including via β-amyloid formation. A series of observables coexist in many chronic, inflammatory diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 340 publications
(378 reference statements)
2
63
0
Order By: Relevance
“…A correlation between P. mirabilis and RA has been observed in multiple patient studies (83); however, the urease/hemolysin hypothesis has not yet been directly tested. Importantly, other microbes have also been linked to RA, and it is possible that there are multiple infectious triggers for RA in vulnerable populations (84). …”
Section: Host Interactionsmentioning
confidence: 99%
“…A correlation between P. mirabilis and RA has been observed in multiple patient studies (83); however, the urease/hemolysin hypothesis has not yet been directly tested. Importantly, other microbes have also been linked to RA, and it is possible that there are multiple infectious triggers for RA in vulnerable populations (84). …”
Section: Host Interactionsmentioning
confidence: 99%
“…For rheumatoid arthritis (142, 458460) and diseases of pregnancy, UTI (see below and Table TT) also provides a major source.…”
Section: Origins Of a Blood And Tissue Microbiomementioning
confidence: 99%
“…These results are of particular importance when it is noted that bacterial involvement might play a role in both the development and progression of PD, and specifically, circulating bacterial inflammagens such as LPS have been implicated (Tufekci et al, 2011;De Chiara et al, 2012;Potgieter et al, 2015;Friedland and Chapman, 2017). We have also suggested that LPS may both maintain systemic inflammation, as well as the disease aetiology itself in PD (but also in other inflammatory diseases like type 2 diabetes, pre-eclampsia, sepsis, rheumatoid arthritis and Alzheimer's disease, where LPS presence has been implicated in the aetiology of the condition) (Kell and Kenny, 2016;Pretorius et al, 2016a;Pretorius et al, 2016b;Pretorius et al, 2017a;Pretorius et al, 2017b;Pretorius et al, 2017c;Kell and Pretorius, 2018b). Indeed in 2018, we showed that LPS from E. coli could be identified with fluorescent LPS E. coli antibodies in clots of PD, type 2 diabetes and AD (de Waal et al, 2018).…”
Section: Amyloid Nature Of Parkinson's Disease Fibrin(ogen)mentioning
confidence: 87%
“…What is not immediately clear is the actual origin of the inflammation and how and why it is chronic. For this and other diseases (Potgieter et al, 2015;Kell and Kenny, 2016;Pretorius et al, 2016a;Pretorius et al, 2017a;de Waal et al, 2018;Kell and Pretorius, 2018a;Kell and Pretorius, 2018b) we have brought together evidence that a chief cause may be (dormant) microbes that upon stimulation, especially with unliganded iron (Kell, 2009), can briefly replicate and shed potent (and well known) inflammagens such as lipopolysaccharide (LPS) and lipoteichoic acid (LTA) Kell and Pretorius, 2018a). These are well-known ligands for receptors such as Toll-like receptor 4 (TLR4) and can thus stimulate inflammation, as observed through a variety of inflammatory cytokines (Olumuyiwa-Akeredolu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%